Digital evaluation of the influence of interruption of the fixation process on radiographic contrast and base-plus-fog density in three commercial brands of radiographic films - Paula Verona Ragusa da Silva; Renan Roberto da Costa; Mariliani Chicarelli da Silva; Lilian Cristina Vessoni Iwaki; Wilton Mitsunari Takeshita
INTRODUCTION : With the interest in anticipating access to the result of intraoral radiography, the radiographic processing is frequently neglected, compromising image quality. OBJECTIVE : The aim of this study was to evaluate the influence of interrupting the fixation process on the radiographic contrast and base-plus-fog density (BPFD) in three brands of periapical films. MATERIAL AND METHOD : Ninety radiographs were taken of an aluminum stepwedge and a lead plate for each brand, and they were divided according to the time of initial immersion in the fixative in: control group (without interrupting the fixing), 5, 10, 20, 30 and 40 seconds. During processing, films had the fixing stage stopped and were exposed to a negatoscope for 1 minute, then the fixation time of 10 minutes was completed. The radiographs were digitized and exported to Image Tool 3.0.software. RESULT : Kodak(r) film showed no statistically significant differences between groups, while Agfa(r) film presented difference in BPFD compared with Group 5 seconds, and Dentix(r) film showed statistical difference in all groups in comparison with the control group. CONCLUSION : Under the conditions studied, Kodak(r) film is not influenced by disruption of fixation as regards BPFD and image contrast, enabling early access to the results of radiographs, whereas Agfa(r) film requires at least 10 seconds of initial fixation, and Dentix(r) film obtains better results when the process of fixation is not interrupted.